Deslocamento de implante dentário para o seio maxilar: relato de caso - Valentini Neto, Rodolpho [UNESP]; Villa, Luiz Marcelo Ribeiro [UNESP]; Bettoni Júnior, Walter [UNESP]; Pellizer, Eduardo Piza [UNESP]; Magro Filho, Osvaldo [UNESP] (My University, 2011)
The residual alveolar ridges may be unfavorable for implant placement. The edentulous maxilla is often challenging for the oral surgeon because of the lack of bone as a consequence of alveolar ridge resorption and/or maxillary sinus pneumatization. Accidents or complications may occur when some of these issues are not being known. This article reports one case of implant displaced into the maxillary sinus, 27 days after sinus bone augmentation with simultaneous dental implant installation, causing moderated sinusitis symptoms. The implant was removed through oral cavity access to maxillary sinus.

Os rebordos alveolares residuais podem ser desfavoráveis para a colocação de implantes. A região posterior de maxila edêntula muitas vezes é desafiadora para o cirurgião oral devido à falta de osso, como conseqüência da reabsorção do rebordo alveolar e/ou pneumatização do seio maxilar. Acidentes ou complicações podem ocorrer quando algumas destas questões não são respeitadas. Este artigo relata um caso de implante deslocado para o interior do seio maxilar, 27 dias após a cirurgia de levantamento de assoalho de seio com instalação concomitante de implante dentário, causando quadro de sinusopatia leve. O implante foi removido por acesso ao seio maxilar por via intrabucal.
Dental implant dislocation to maxillary sinus: case report
Keywords: Dental implants; |Postoperative complications; Maxillary sinus; Implantes dentários; Complicações pós-operatórias; Seio maxilar